Unusual Length of Pedicle: Pedunculated Squamous Papilloma of Uvula Causing Unusual Dysphagia of Long Duration in a Child of 10 Years - Ramisetty Sabitha Devi; B. Rajsekhar; G. Vijay Srinivas; Ninad J. Moon (Case Reports in Dentistry)
Benign oropharyngeal tumors are far less common compared to malignant tumors. Oropharyngeal papilloma is present in adults. Squamous papillomas are exophytic masses of oral cavity. When they occur on the palate they are most often asymptomatic and benign. Pedunculated squamous papillomas usually arise from the soft palate, tonsil, or the epiglottis. These lesions can sometimes prove to be fatal. A case of pedunculated squamous papilloma, arising from the laryngopharynx, the clinical presentation, the site of origin, and the size of the lesion were quite unusual. The narrow base of the pedicle made the intraoral excision possible. But here, we present a case of a 10-year-old boy who had history of dysphagia of 3-year duration for solid food and he was comfortable only in squatting position the reason being squamous papilloma of uvula (unusual site) atypically because of astonishing length of pedicle (2.3 inches).